1983
DOI: 10.1128/iai.40.2.460-463.1983
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of plasmid DNA in serologically defined strains of Campylobacter jejuni and Campylobacter coli

Abstract: Forty Campylobacter jejuni and 17 Campylobacter coli strains that constitute the set of reference strains for our serotyping scheme were each examined for the presence of plasmid DNA. Agarose gel electrophoresis of alkaline-extracted DNA showed the occurrence of 29 bands in 11 C. jejuni strains and 40 bands in C. coli strains. Plasmids ranged in size from 1.6 to 70 megadaltons. Most strains that carried plasmids had between 2 and 6 of them; however, one strain had 14 plasmids, and two strains contained only 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 22 publications
0
22
1
Order By: Relevance
“…Even this drastic measure may not solve the problem, however, as plasmids may appear in a higher size range than 125 kb, either because they actually are that large ("megaplasmids") or because they have not been digested by the restriction enzyme used and are not in a linear conformation (Barton et al, 1995). It is wellknown that plasmids, including megaplasmids, are common in foodborne pathogens (Bradbury et al, 1983;Wachsmuth et al, 1991;Olsen et al, 1994;Barton et al, 1995;Iteman et al, 1996;McLauchlin et al, 1997), but the influence of the plasmid content on the PFGE profiles of foodborne pathogens has not been well characterized.…”
Section: Tenover Criteria and Sources Of Variability In Pfge Patternsmentioning
confidence: 99%
“…Even this drastic measure may not solve the problem, however, as plasmids may appear in a higher size range than 125 kb, either because they actually are that large ("megaplasmids") or because they have not been digested by the restriction enzyme used and are not in a linear conformation (Barton et al, 1995). It is wellknown that plasmids, including megaplasmids, are common in foodborne pathogens (Bradbury et al, 1983;Wachsmuth et al, 1991;Olsen et al, 1994;Barton et al, 1995;Iteman et al, 1996;McLauchlin et al, 1997), but the influence of the plasmid content on the PFGE profiles of foodborne pathogens has not been well characterized.…”
Section: Tenover Criteria and Sources Of Variability In Pfge Patternsmentioning
confidence: 99%
“…Following the procedure of KADO and LIU (17), with some modifications (4,7,9,27), several large colonies from overnight cultures on brain-heart infusion agar or sheep blood agar were suspended in 20 p1 of E-solution (40 mM tris p H 7.9 + 2 mM EDTA) to which 100 p1 of lysis solution (3 % SDS + 50mM trisacetate in 100ml distilled water (pH 12.2) were added. The solution was emulsified by brief shaking and gentle inversion for several times.…”
Section: Preparation Of Plasmid Dnamentioning
confidence: 99%
“…are being developed: that of Lior et al (17) dealing with C. jejiuni, in which 14 to 17% of the strains examined were found to be untypable, and another system devised with both C. jejluni and C. coli in mind (21). Certain difficulties with the latter system have been encountered, and it has been suggested that plasmid typing may be necessary as an additional means of discrimination (5).…”
mentioning
confidence: 99%